VALUE OF ECOLOGICAL INTELLIGENCE IN LETTUCE IN DISTRICT PARONGPONG DISTRICT BANDUNG BARAT - Mainaki, Revi (Indonesia University of Education, 2017)
Environmental degradation makes people affected of damage to the environment itself. One of suggested solution is the development of ecological intelligence. The forms of ecological intelligence can be seen on lettuce farmer’s behavior in Parongpong District, West Bandung Regency. The farmer has a variety of knowledge about environmental pollution by seeing the harvest of lettuces, in terms of the attitude of the population to prohibit and do not agree with everything that is damaging to the environment Participation of the residents in conducting environmental conservation is evident from modifying land by taking into account the possible risk of damage. We can learn the values of ecological intelligence watercress farmers in Sub Parongpong, West Bandung Regency to improve ecological intelligence as one of the solutions to problems are local but able to be generalized in the form of global.